Politik Hukum Larangan Kepemilikan Hak Atas Tanah di Daerah Istimewa Yogyakarta Oleh Warga Negara Indonesia Keturunan Tionghoa Dan Dampak Terhadap Komparisi Akta Jual Beli - Dhimas Yuki Hananto Adhi; Nurwidiatmo N (Jurnal Nuansa Kenotariatan, 2020)
Law Number 5 of 1960 (UUPA), is a legal instrument that regulates land affairs and creates a single national land law. Basically an individual can have land rights, in Article 21 paragraph 1 states that the subject of ownership is an Indonesian citizen, right of ownership can be transferred, one of which is through the sale and purchase with proof of sale and purchase deeds made by the Acting Authority, and the referral to Government Regulation Number 8 of 2012, Articles 1320 and 1868 of the Civil Code , and how to register it according to Government Regulation Number 24 of 1997 and State Minister of Agrarian Regulation Number 3 of 1997. The method used in this research is the normative juridical research method supported by Empirical Juridical. Based on the results of this study it was concluded that Political Law through Instructions 898/I/V/A/1975 concerning the prohibition of ownership of land rights by Indonesian citizens of Chinese descent carried out by the Special Region of Yogyakarta to protect indigenous people who are economically weak, even though it is contrary to the Law Principal of Agrarianism, because ethnic Chinese are considered to be superior in financial terms, a form of positive discrimination is a form of the Sultan’s wish as the High Leader of Yogyakarta in protecting its financially weak people and the Deed of sale and purchase in the city of Yogyakarta that has been signed by the parties, witnesses as well as land deed officials, are not obliged to include the phrase Indigenous/ Non-Indigenous as long as the Land Deed Makers Officer makes a New Legal Document namely a statement that the sale and purchase is done by being able to reduce the Property Rights to another right for Indonesian citizens of Chinese descent, selling can be done by n the requirement that land ownership has become a Building Use Right if it does not have to start with the PPJB or the deed of release